Reduced antimicrobial consumption through enhanced pneumonia management in critically ill patients: outcomes of an antibiotic stewardship program in the intensive care unit - Sekandarzad, Asieb; Flügler, Annabelle; Rheinboldt, Anne; Rother, David; Först, Gesche; Rieg, Siegbert; Supady, Alexander; Lother, Achim; Staudacher, Dawid Leander; Wengenmayer, Tobias; Kern, Winfried V.; Biever, Paul Marc (Frontiers in Medicine, 2025)
BackgroundCritically ill patients in the intensive care unit (ICU) who are suspected of having pneumonia are frequently treated with broad-spectrum antimicrobials even when the diagnosis remains uncertain. While appropriate antimicrobial therapy offers undeniable benefits, its inappropriate or excessive use can lead to harmful side effects. This study examines the impact of an antimicrobial stewardship program (ASP) in the ICU on both diagnostic accuracy and antimicrobial consumption in critically ill patients with pneumonia.MethodsThis cohort study compares a prospective cohort with matched controls from a retrospective sample in the ICU of a tertiary hospital. An ASP was implemented focusing on microbiological sampling of bacteria and antimicrobial therapy. Primary endpoint was days of therapy (DOTs). Secondary endpoints were number of respiratory samples (RS), identification of relevant bacteria in RS and diagnostic accuracy of pneumonia. Clinical safety outcome parameters were length of stay, length of invasive mechanical ventilation and ICU mortality until day 28.ResultsA total of 200 patients were assigned to the intervention group (IG) and 200 to the control group (CG). The overall DOTs per patient were 12.95 [95% confidence interval (CI) 11.42 to 14.47] in the CG compared to 9.91 (CI 8.97 to 10.82) in the IG (p = 0.036), with no unfavorable findings in safety outcome parameters. DOTs for meropenem were 2.74 (CI 2.14 to 3.34) in the CG vs. 1.13 (CI 0.76 to 1.49) in the IG (p < 0.001), DOTs for piperacillin/tazobactam were 3.66 (CI 3.16 to 4.15) vs. 2.78 (CI 2.33 to 3.22; p = 0.011), and DOTs for ampicillin/sulbactam were 1.49 (CI 1.15 to 1.82) vs. 2.63 (CI 2.25 to 3.02; p < 0.001). Relevant bacteria in RS were detected more frequently in the IG, with n = 91 compared to n = 61 in the CG (p = 0.003).ConclusionImplementation of an ASP in the ICU effectively reduces broad-spectrum antimicrobial consumption in critically ill patients with pneumonia without compromising patient safety.